Produção de anticorpos monoclonais contra os componentes conservados do vírus da bronquite infecciosa das galinhas - Cleiton Martins de Souza (2000)
Murine hybridomas producing lgG1 monoclonal antibodies (Mab) against N and S2 proteins (53KDa and 82KDa, respectively from avian infection bronchitis virus (IBV) strain M41 (serotype Massachusetts) were generated by the fusion of a myleoma cell line (Sp2/0-Ag 14) with spleen cells from Balb/c mice previously immunized with whole virus IBV M41. Post-fusion screening criterion was based on ELISA and 36 positive hybrids producing Mab to IBV M41 were generated after two fusion producers. The Mab specific to N (N3F10) and S2 (S12B2) proteins of M41 were selected by western blotting. These Mabs were able to recognize the Ark-99 (serotype Arkansas) and A5968 (serotype Connecticut) IBV strains in addition to M41. By ELISA, the Mab against the S2 (S12B2) glycoprotein recognized all Brazilian isolates (297, 283, PM-1, PM-2, PM-2, 351, 29-78 e 327) studied, while the Mab against the N protein recognized only six (M41, SE-17, H52, 283, 327 e 297) isolates. The Mab against S2 may became a useful tool for IBV detection on the routine diagnosis of infectious bronchitis, especially for helping the differential diagnosis of clinically and pathologically confusing diseases. The Mab N3F10 was able to recognize a less conserved region of N, evidenciating differences among isolates which may enable the use of N3F10 for phylogenetic studies of IBV